ZnS anisotropic nanocrystals using a one-pot low temperature synthesis. (30th October 2014) - Buffard, Aude; Nadal, Brice; Heuclin, Hadrien; Patriarche, Gilles; Dubertret, Benoit
Abstract : Low temperature, scalable and air stable synthesis of ZnS nanowires and nanoplatelets. Abstract : We report a simple, low temperature and scalable synthesis of wurtzite ZnS anisotropic nanocrystals performed under air. The reaction between a zinc salt (nitrate or chloride) with thioacetamide and amines at 60 °C yields ZnS nanoplatelets or nanowires absorbing in the ultra-violet region with a full width at half maximum between 11 nm and 15 nm.